Complete mitochondrial genome of Chinese icefish Neosalanx tangkahkeiis (Salmoniformes, Salangidae): comparison reveals Neosalanx taihuensis not a valid name. (2nd September 2016) - Zhong, Liqiang; Wang, Minghua; Li, Daming; Tang, Shengkai; Zhang, Tongqing; Bian, Wenji; Chen, Xiaohui
Abstract: The complete mitochondrial genome of Neosalanx tangkahkeiis was determined to be 16, 550 bp in length with (A+T) content of 49.7%, and it consists of 13 protein-coding genes, 22 tRNAs, 2 ribosomal RNAs, and a control region. The gene composition and the structural arrangement of the N. tangkahkeiis complete mtDNA were identical to most of other vertebrates. The sequence comparison showed that mitogenome of N. tangkahkeiis had a 99.9% of similarity with so-called N. taihuensis, indicating they are the same species and N. taihuensis is not a valid name.